Letter to the editor: integrative approach to knee osteoarthritis management - Abhimanyu (International Journal of Research in Orthopaedics, 2025)
The study provides compelling evidence supporting the synergistic benefit of combining physiotherapy with pharmacologic therapy for managing knee osteoarthritis (OA). The authors have appropriately highlighted that monotherapies-whether pharmacologic or rehabilitative-may offer limited benefit in comparison to a structured dual-modality approach.